Effect of Imbibition Time on Hormonal Changes of Germinating Tamarindus indica and Prosopis juliflora - B. A. Kyari; Z. A. Lawan; M. S. Waziri; H. M. Ajiri; B. Apagu; H. Mari; M. A. Ibrahim (Indonesian Journal of Agricultural Research, 2022)
Imbibition time and hormonal changes play a significant role in seed germination. This study, evaluated the effects of some phytohormones; indole acetic acid (IAA), abscisic acid (ABA), gibberellin and cytokinins) and imbibition time (0, 48 and 96 hours) on Tamarindus indica and Prosopis juliflora. High-Performance Liquid Chromatography (HPLC) was used to determine the concentrations of the hormones. Results indicated significantly higher and faster in P. juliflora than T. indica. The germination rate was 4.1 - 68.1% and 4.0 - 61.4%, and model for inhibition time 28.256ln(x) and 25.791ln(x), respectively. Similarly, results also expressed highly significant variable changes in the concentrations of the four studied phytohormones between T. indica (0.491 - 0.705 mg/ml) and P. Juliflora (0.109 - 1.130 mg/ml). The concentrations of IAA and ABA were significantly higher by 60.6% and 77.7% in the seeds of T. indica than P. juliflora, respectively. P. juliflora had 37.6% and 12.5% higher cytokinin and gibberellin than T. indica, respectively. Cytokinin (0.7951 - 1.0939 mg/ml), gibberellins (0.535 - 0.757 mg/ml), IAA (0.363 - 0.419 mg/ml) and ABA (0.250 - 0.335 mg/ml) also varied significantly over the periods. In general, cytokinin and gibberellins increased by 8.1 - 27.3% and 22.9 - 23.0%, while that of IAA and ABA decreased 13.6 - 15.4% and 26.4 - 34.0%, over the imbibitions time of 0-96 hours. In conclusion, higher germination of P. juliflora is attributed to cytokinin and gibberellins, and the lower germination in T. indica to the higher inhibitory effects of IAA and ABA.